African Initiated Churches" potential as development actors - Öhlmann, Philipp (HTS teologiese studies, 2016)
African Initiated Churches (AICs) are not yet recognised as relevant actors of community development interventions. While it has been acknowledged that many of them provide coping mechanisms in adverse environments, support in social transformation and social capital, little information is available on their role as development actors. In this article, we evaluate the potential of AICs as partners of international development agencies for community development. We draw on interviews and focus group discussions with leaders of various AICs conducted in South Africa in February and March 2016. In particular, we examine the churches’ understanding of development, their view on the separation of spiritual and development activities and their priorities. Moreover, we outline the development activities which they are currently engaged in and analyse the structures they have in place to do so. Our findings indicate that AICs are increasingly active in community development and offer various entry points for possible cooperation.